Transient fluid flow and heat transfer over a rotating circular cylinder near a wall subject to a single gust impulse. (November 2018) - Hanif, Rabia; Bhatti, O.G.; Ebrahem, M.; Manzoor, S.; Ali, Muzaffar; Sheikh, N.A.
Highlights: Effect of gust is numerically studied on rotating cylinder near a plane wall. Plane wall boundary layer is affected even at larger values of G/D i.e. 3. Temporary convection zones affect the heat transfer from the cylinder surface. Abstract: Numerical results are presented investigating the effect of a gust impulse on the transient fluid flow and forced convection heat transfer from a rotating circular cylinder near a plane boundary in the two-dimensional, in-compressible flow regime. Reynolds numbers of 200, 600 and 1000 have been studied for a fluid of Prandtl number 7. Starting from static, the steady non-dimensional rotation rate is varied up to a maximum value of 5.5, in the counter clockwise direction, such that ( α ∈ 0, 0.5, 1, 2, 2.5, 4.7, 4.9, 5, 5.5 ) . Gap to diameter ratio for this work is fixed at 3. Typical governing equations namely continuity, momentum and energy have been solved using the Constant Wall Temperature (CWT) boundary condition. This work notes that higher rotation rate of the circular cylinder, in the second vortex shedding regime and slight perturbations in the flow may cause a resultant effect which leads to short term disruption in the plane wall boundary layer dynamics even at larger values of gap to diameter ratio. Moreover, the gust impulse superimposed to the mean flow at the domain inlet causes creation of temporary convection zones in the cylinder wake which have significant impact on the heat transfer from the cylinder surface. Variations in Strouhal number, vorticity contours, peak vorticity trajectory plots, temperature contours and Nusselt number distribution are presented and discussed in comparison with the existing literature.